Alpha lipoic acid attenuates evoked and spontaneous pain following surgical skin incision in rats - Joksimovic, Sonja Lj. (Channels (Austin), 2021)
Our previous studies have implicated Ca(V)3.2 isoform of T-type Ca2+ channels (T-channels) in the development of postsurgical pain. We have also previously established that different T-channel antagonists can alleviate in vivo postsurgical pain. Here we investigated the analgesic potential of another T-channel blocker and endogenous antioxidant molecule, α-lipoic acid (ALA), in a postsurgical pain model in rats. Our in vivo results suggest that single and repetitive intraperitoneal injections of ALA after surgery or preemptively, significantly reduced evoked mechanical hyperalgesia following surgical paw incision. Furthermore, repeated preemptive systemic injections of ALA effectively alleviated spontaneous postsurgical pain as determined by dynamic weight-bearing testing. We expect that our preclinical study may lead to further investigation of analgesic properties and mechanisms of analgesic action of ALA in patients undergoing surgery.